Fluid Metabolism in Athletes Running Seven Marathons in Seven Consecutive Days - Chlíbková, Daniela; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat; Bednář, Josef (Frontiers in Physiology, 2018)
Purpose: Hypohydration and hyperhydration are significant disorders of fluid metabolism in endurance performance; however, little relevant data exist regarding multi-stage endurance activities. The aim of the present study was to examine the effect of running seven marathons in seven consecutive days on selected anthropometric, hematological and biochemical characteristics with an emphasis on hydration status. Methods: Participants included 6 women and 20 men (age 42.6 ± 6.2 years). Data was collected before day 1 (B1) and after day 1 (A1), 4 (A4), and 7 (A7). Results: The average marathon race time was 4:44 hour:min (ranging from 3:09 to 6:19 hour:min). Plasma [Na+], plasma [K+] and urine [Na+] were maintained during the race. Body mass (p < 0.001, η2 = 0.501), body fat (p < 0.001, η2 = 0.572) and hematocrit (p < 0.001, η2 = 0.358) decreased. Plasma osmolality (Posm) (p < 0.001, η2 = 0.416), urine osmolality (Uosm) (p < 0.001, η2 = 0.465), urine [K+] (p < 0.001, η2 = 0.507), urine specific gravity (Usg) (p < 0.001, η2 = 0.540), plasma urea (PUN) (p < 0.001, η2 = 0.586), urine urea (UUN) (p < 0.001, η2 = 0.532) and transtubular potassium gradient (p < 0.001, η2 = 0.560) increased at A1, A4, and A7 vs. B1. Posm correlated with PUN at A1 (r = 0.59, p = 0.001) and A4 (r = 0.58, p = 0.002). The reported post-race fluid intake was 0.5 ± 0.2 L/h and it correlated negatively with plasma [Na+] (r = -0.42, p = 0.007) at A4 and (r = -0.50, p = 0.009) at A7. Uosm was associated with UUN at A1 (r = 0.80, p < 0.001), at A4 (r = 0.81, p < 0.001) and at A7 (r = 0.86, p < 0.001) and with Usg (r = 0.71, p < 0.001) at A1, (r = 0.52, p = 0.006) at A4 and (r = 0.46, p = 0.02) at A7. Conclusions: Despite the decrease in body mass, fluid and electrolyte balance was maintained with no decrease in plasma volume after running seven marathons in seven consecutive days. Current findings support